2020
DOI: 10.1029/2019jd031789
|View full text |Cite
|
Sign up to set email alerts
|

A New Detailed Plasma‐Chemistry Model for the Potential Impact of Blue Jet Streamers on Atmospheric Chemistry

Abstract: A detailed ion-neutral chemistry model named MiPO-Streamer model has been developed to simulate the impact of blue jet streamers on stratospheric chemistry. It is based on the MiPLaSMO model (Microphysical and Photochemical Lagrangian Stratospheric Model of Ozone) widely used over the last 20 years to interpret balloon and satellite measurements associated with stratospheric ozone. In this study, instead of using a reduced electric field with constant value during blue jet streamer discharge process, we used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…In section IV-A, the ChargedSpecies() class was described, which is used to define a single charged species. However, in many nonthermal plasma applications, e.g., [7], [15], knowledge of the plasma composition, and of the exact combination of charged species developed during a discharge, is of critical importance. Manual definition of each individual species using ChargedSpecies() would be tedious and error-prone.…”
Section: E Problem Generation and Plasma Chemistry Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…In section IV-A, the ChargedSpecies() class was described, which is used to define a single charged species. However, in many nonthermal plasma applications, e.g., [7], [15], knowledge of the plasma composition, and of the exact combination of charged species developed during a discharge, is of critical importance. Manual definition of each individual species using ChargedSpecies() would be tedious and error-prone.…”
Section: E Problem Generation and Plasma Chemistry Inputmentioning
confidence: 99%
“…Specialized schemes using custom codes, employing techniques which are particularly effective for multiscale modelling have also been developed, and demonstrate major advances in computational efficiency and speed [13], [14]. The popularity of these methods has grown rapidly, with models that incorporate aspects such as complex plasma chemistry [15], nonuniform electric fields [16], and solid dielectric boundaries [17], [18], becoming increasingly prevalent. Currently, the software developed must typically strike a balance between issues such as computational speed, resource usage, accessibility, adaptability, accuracy, and model fidelity.…”
mentioning
confidence: 99%
“…3 of 15 bromine chemical families associated with stratospheric ozone as well as the ions and excited species. A detailed description of the streamer part of the model and its validation exercise at 27 km can be found in Xu et al (2020). To investigate the chemical processes associated with a single streamer and leader of BJ, the effect of convection is not considered in this model.…”
Section: 1029/2023jd038668mentioning
confidence: 99%
“…Compare to the model studies of Mishin (1997), Smirnova et al (2003), and Winkler and Notholt (2015), Xu et al (2020) developed a detailed plasma chemistry model for representing the BJ streamer, which used the realistic reduced electric field and performed the simulation over several days. Xu et al (2020) only revealed the chemical impact of BJ streamer at 27 km, and did not consider the impact of BJ leader and these impacts on the whole stratospheric profile. Winkler and Notholt (2015) did a model study on the chemical impact of BJ leader.…”
mentioning
confidence: 99%
“…Nous ne pouvons pas prendre les taux de réaction inverse et direct directement dans la littérature. En effet, les taux de réaction sont souvent mal connus et doivent être choisis avec précaution [11] et il est nécessaire d'obtenir la concentration de l'équilibre chimique lorsque le mélange est stable dans le temps. C'est-à-dire au bout d'un temps suffisamment long.…”
Section: Calcul Des Concentrations Chimiquesunclassified